Virtual Supervisi Akademik Pada Masa Pandemi Covid 19 Di Madrasah Aliyah Kota Padang: VIRTUAL SUPERVISI AKADEMIK PADA MASA PANDEMI COVID 19 DI MADRASAH ALIYAH KOTA PADANG - Hasnawati (Proceedings of Annual Conference on Islamic Educational Management, 2021)
During the Covid 19 pandemic, the academic supervision was not carried out properly because 47,5% of the supervision activities were conducted through zoom meeting. The research method is qualitative-descriptive using NVIVO12 software. This sampling technique is popusive sampling. The number of samples consisted of 40 Madrasah aliyah in the city of Padang with 200 supervisors as participants. Method of data collection with open interviews conducted virtually (Zoom, Google Meet).The findings indicate that there were sixteen online platforms used in the academic supervision such as Whatsapp group, Zoom, Google Meets, Edmodo, Google Classroom, Video Call, Email, E-Learning, Webex, Facebook, Schoology, Padlet, Microsof Team, Moodle, blog, You Tube. Seen from the percentage of use, Whatsapp platform was most widely used in virtual learning during the COVID 19 pandemic with 51 users or 25.5%, Zoom Meeting 89 or 47,5%,  Google Meet 28 or 14.0%, Email 18 or or 9.0%,  Microsoft Teams 3 or 1.5%, respectively. The problems faced during this process included unstable signals, limited data package, passive teachers, less supporting school server, low internet condition, and less supporting applications. In addition, some supervisors did not fully understand information technology and had difficulties in arranging supervision schedules in some places due to the unexpected electrical problems. Research location in Madrasah aliyah in the city of Padang